EVALUASI IMPLEMENTASI PROGRAM INDONESIA PINTAR DI SMA NEGERI 1 SEMBAWA - Hayati, Nurhasana; Sari, Eka Yuliana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The Smart Indonesia Program is an effort made by the government for educational equity. This study aims to evaluate the implementation of the Smart Indonesia Program (PIP) at SMAN 1 Sembawa, including program targets, program benefits, and constraints that arise in the mechanism of implementing a smart Indonesia program (PIP). In this study the researcher used descriptive qualitative research methods by collecting data, interviews, documents and library sources as primary data sources and secondary data. The results of the study can be concluded that the implementation of the Smart Indonesia Program (PIP) at SMAN 1 Sembawa has not run optimally as it should be, this can be seen from: 1) There are still many students who receive PIP funds that are not on target, this is because the data used in determining the prospective recipients of KIP or PIP is still inaccurate, 2) Still low awareness of students and parents of students about the allocation of PIP funds, 3) Time of disbursement of PIP funds that are late due to lack of socialization 4) Difficult mechanism for disbursing PIP funds.